Intraday exchange rate volatility transmissions across QE announcements - Dimitris Kenourgios; Stephanos Papadamou; Dimitrios Dimitriou (Finance Research Letters, 2015)
This paper examines the effects of quantitative easing (QE) announcements by the European Central Bank (ECB), the Bank of England (BoE) and the Bank of Japan (BoJ) on the intraday volatility transmissions among EUR, GBP and JPY. The empirical results indicate: (i) an increased volatility transmission from EUR to JPY and GBP around the ECB announcements, and from GBP to EUR over the BoE announcements, (ii) the ECB and BoE announcements significantly increase the volatility of EUR and JPY, and (iii) a ‘‘calming down’’ impact on the volatility of EUR and GBP from the BoJ and the ECB announcements, respectively.